The Effect Of PBL Model On Learning Outcomes Theme 5 Subtheme 3 Learning 1 In Grade 3 - Siti Nur Khoirun Nisak; Desty Dwi Rochmania (Prodi PGSD Fakultas Ilmu Pendidikan (FIP) Universitas Hasyim Asy'ari (Unhasy) Tebuireng Jombang, 2022)
This study aims to determine student learning outcomes of critical thinking before using the PBL model on theme 5 sub-theme 3 learning 1 in grade 3 SDN Gedangan Student learning outcomes in critical thinking after using the PBL model on theme 5 sub-theme 3 learning 1 in grade 3 SDN Gedangan 1, and To find out the response after learning to think critically using the PBL model on theme 5 sub-theme 3 learning 1 in grade 3 SDN Gedangan 1. The results of this study are expected to provide ideas that can be used as a source of information to increase knowledge, as well as input and consideration for institutions that related to the PBL learning model. The design of this study was pre-experimental and the design used was a one group pretest-posttest design. The research subjects were 3rd grade students of SDN Gedaangan 1 Sumobito Jombang for the academic year 2021/2022. Data collection techniques using tests. The study was conducted in the even semester of January 2022. Students were given pre-test and before learning using the PBL learning model in learning theme 5 sub-theme 3 learning 1 in grade 3 SDN Gedangan 1, from the pretest and posttest tests carried out, the average pretest result was 62 with 18 students scored below the KKM and 16 students scored above the KKM, while the posttest average was 90, none of the students scored below the KKM. The positive response of student questionnaire data is 68.6%. These results indicate that the use of the PBL model in learning theme 5 sub-theme 3 learning 1 in class III SDN Gedangan 1 can have a positive effect on student learning outcomes and interest in learning. Keywords: PBL Model, Critical Thinking Learning Outcomes